Uji Aktivitas Krim Anti-Aging Ekstrak Etanol Daun Bayam Merah (Amaranthus tricolor L.) pada Kulit Punggung Kelinci New Zealand yang dipapar Sinar UV-A - Ananda Rezky Putri; Suhartinah Suhartinah; meta kartika (Indonesian Journal of Pharmaceutical Education, 2023)
The strongest cause of premature aging is sunlight (photoaging), especially UV A rays. Anti-aging creams containing antioxidant compounds can be used in the treatment of aging on the skin of the face. Red spinach leaves (Amaranthus tricolor L.) are a natural source of antioxidants that have very strong potential as an anti-aging. Objectives: This study aims to determine the activity of red spinach leaf extract cream as an anti-aging using New Zealand rabbits exposed to UV-A rays. The skin of the rabbit's back is smeared with cream F1, F2, F3, F4, F5 for 30 days. Parameter observation using a skin analyzer is carried out before, after induction, and after cream smearing. Parameters include percent collagen, elasticity, and moisture. The results of the study were analyzed statistically using one way anova. All test creams pass the physical quality test requirements, but the creams that pass the stability test are F1, F2, F4. The primary irritation test F1, F2, F4 is not irritating whereas F3 is very little irritating. Test the ocular irritation of all creams is not irritating. The test results of anti-aging activity show that F2 provides the most effective anti-aging effect because the percent increase in parameters is the greatest.